Heat capacity of ethylene carbonate and ethyl methyl carbonate for the liquid phase at elevated temperatures - Philipp Finster; Judith Jung; Magnus Rohde; Hans Jürgen Seifert; Carlos Ziebert (Chemical Thermodynamics and Thermal Analysis)
The heat capacities of liquid ethylene carbonate (EC) and ethyl methyl carbonate (EMC), two important electrolyte components for capacitors and Lithium-ion-batteries, were measured using differential scanning calorimetry in the temperature range from 263 to 500 K in heating mode and from 493 to 273 K in cooling mode for EC. The effect of the supercooled liquid of EC on the heat capacity is discussed. The heat capacity of EMC was determined from 211 to 360 K in heating mode. Based on the obtained heat capacities and the literature data, a simplified Maier–Kelley-fit for the heat capacities is provided. The temperature range of the experimentally determined heat capacity of the liquid state was extended to higher temperatures than previously reported in literature.